انعكاس التحول الرقمي على استراتيجية تصميم نظم المعلومات المحاسبية: من وجهة نظر موظفي وزارة المالية - محمد عبدالرحمن محمد قباصة; عدنان عياد عمر الغليظ (Surman Journal of Science and Technology, 2025)
The study aimed to understand the impact of digital transformation on the accounting information systems design strategy. The theoretical aspect of the study relied on a descriptive and analytical approach. The field study involved distributing a questionnaire to a sample of Ministry of Finance employees. The study concluded that digital transformation plays a fundamental role in improving accounting transactions and activities, enhancing the efficiency of accounting systems, and strengthening the accounting information systems strategy. The study recommended a number of recommendations, most notably the need to develop the digital infrastructure in financial institutions and provide advanced electronic protection systems that ensure data security and confidentiality.